As possibilidades da Revolução em Ellul - Barrientos-Parra, Jorge David [UNESP] (My University, 2014)
The author, based on the work Change of Revolution, analyzes what Jacques Ellul understand as structural and existential in a Marxist revolution. Analyzing the main experiences of this type, the French thinker finds its by technification of the society. However, it also notes the validity of Marx’s objectives of overcoming the proletariat and the alienation. Thus, a revolutionary and libertarian socialism would be possible under certain conditions. On an existential level, Ellul questions in each one of us the permanence of efficiency values, of power and the pursuit of money as the main purpose of life, offering an authentic and radical transformation before the seizure of power. Thus, the author develops the Ellulian concept of God’s revelation in Jesus Christ as a lever and fulcrum of Revolution.

O autor, tendo como base a obra Mudar de Revolução, analisa, neste texto, em caráter preliminar, o que Jacques Ellul entende como sendo o estrutural e o existencial numa revolução marxista. Analisando as principais experiências desse tipo, o pensador francês constata o seu fracasso a partir da opção pela tecnicização da sociedade. Entretanto, constata também a validade dos objetivos de Marx de superação do proletariado e da alienação. Assim, um socialismo revolucionário e libertário seria possível dentro de determinadas condições. No plano existencial, Ellul questiona em cada um de nós o arraigo dos valores da eficácia, do poderio e da busca do dinheiro como principais finalidades da vida, propondo uma autêntica e radical transformação antes da tomada do poder. Dessa forma, o autor desenvolve o conceito elluliano da revelação de Deus em Jesus Cristo como alavanca e ponto de apoio da revolução.
The chances of Revolution in Ellul
Keywords: Change of Revolution; Socialism; Sociology of Technique; Scopes of the Revolution; Biblical revelation; Teachings of Jesus; Christian ethics; Agape; Mudar de Revolução; Socialismo; Sociologia da Técnica; Âmbitos da Revolução; Revelação Bíblica; Ensinos de Jesus; Ética cristã; Amor ágape